Pengaruh ROA, ROE, dan DER terhadap Profitabilitas Perusahaan Personal Care yang Terdaftar di Bursa Efek Indonesia Tahun 2021 – 2024 - Jarmadi Setiawan; Bayu Kurniawan; Noni Setyorini (Pajak dan Manajemen Keuangan, 2025)
Profitability is a key indicator in assessing a company’s financial performance, particularly in the personal care industry listed on the Indonesia Stock Exchange (IDX). This study aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER) on profitability as measured by Net Profit Margin (NPM). The research employed a quantitative approach using multiple linear regression analysis based on the financial statements of personal care companies for the 2021–2024 period. The findings reveal that ROA has a positive and significant effect on NPM, indicating that the more efficiently a company manages its assets, the higher the net profit margin achieved. Meanwhile, ROE and DER show no significant effect on NPM, implying that shareholder equity returns and debt utilization in the capital structure have not directly enhanced net profitability. These results suggest that optimal asset management is a crucial factor in improving the financial performance of personal care companies.